Angolanity and angolanization: linkages of governance in the post-civil war in Angola - Gaio, Gabrieli Fernandes Fickelsherer (ODEERE, 2016)
This article aims to analyze the interaction between the conception of angolanidade and the recent process of angolanização in Angola’s economy. The present work brings a brief historical approach regarding cultural policy and political economy in the country, covering such subjects since the struggle for independence. Special attention is given to the years following the end of Angola’s civil war, when cultural policies as well as angolanização gained prominence in the government’s agenda setting, giving rise to a complex link with the historic construction of angolanidade as a national identity. This work explores the way in which angolanidade and angolanization transcend the boundaries of policies that envisage, respectively, the cultural and the economic sectors in order to integrate a governance complex feautured by the urgencies and dynamics of Angola’s nation building under a pluriethnic context. Keywords: culture; cultural policies; nationalism; angolanidade; angolanização.